(untitled) - Kemeny, T. G. (New Jersey, 1960)
The restriction of this book to finite chains has made it possible to give simple, closed-form matrix expressions for many quantities usually given as series. It is shown that it suffices for all types of problems to consider just two types of Markov chains, namely absorbing and ergodic chains.
Keywords: Markov processes,Quy trình Markov